Fast‐food addiction and anti‐consumption behaviour - Farah, Maya F. (2020)
This study aims to understand the drivers of fast‐food addiction and the role of consumer social responsibility (CSR) on the relationship between fast‐food addiction and anti‐consumption. Due to growing health concerns, an increasing number of consumers have been avoiding the consumption of fast food. Based on a sample of 539 respondents, all pertaining to generation Y in Pakistan, this study tests a model including addiction and anti‐consumption behaviour. Empirical results provide strong evidence that individual and sociocultural factors together with advertising practices influence consumers’ fast‐food addiction. Results also reveal that CSR moderates the relationship between fast‐food addiction and anti‐consumption behaviour. Interestingly, the present study pioneers the discussion on how addiction can drive anti‐consumption. The findings can help public policy makers and managers to understand consumers’ anti‐consumption tendencies and help promote healthier consumption habits.